1989
DOI: 10.1116/1.576341
|View full text |Cite
|
Sign up to set email alerts
|

Polymer surface reactivity enhancement by ultraviolet ArF laser irradiation: An x-ray photoelectron spectroscopy study of polytetrafluoroethylene and polyethyleneterepthalate ultraviolet treated surfaces

Abstract: We have investigated by x-ray photoelectron spectroscopy (XPS) the surface of two polymers [polytetrafluoroethylene and polyethyleneterepthalate (PTFE) and (PET)] which were previously submitted to pulsed UV radiation delivered from an excimer laser (ArF: λ=193 nm). Treatments realized under different gaseous atmospheres allow us to point out mechanisms leading to several chemical transformations at the polymer surface. In the case of PTFE, the high-fluence irradiations produce defluorination with surface oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…6. In this work, surface oxidation of polymer film due to the moisture in air can be avoided since the laser irradiation was performed under nitrogen flow [17]. It has been reported that under highenergy UV-laser irradiation, the decomposition fragments of PTFE consisted almost entirely of monomer (C 2 F 4 ) [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6. In this work, surface oxidation of polymer film due to the moisture in air can be avoided since the laser irradiation was performed under nitrogen flow [17]. It has been reported that under highenergy UV-laser irradiation, the decomposition fragments of PTFE consisted almost entirely of monomer (C 2 F 4 ) [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the molecular structure of fluoropolymer contains only high energy → * and n → * transitions that result in poor UV absorption. The PTFE with highly stable molecular structure is a weak absorber with an absorption coefficient of 158 cm −1 at 248 nm [17][18][19]. Although the utilization of the nitrogen flow over the sample during laser irradiation trends to increase the threshold, it is necessary to avoid the redeposition of the ablated material and to obtain clean ablated walls and bottom morphologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the preparation of PFEP molecule, three new peak components at 290.2 eV, 291.3 eV, and 294.2 eV are clearly observed, as shown in spectrum 7a. The three peaks originate from the -CF 2 -CH 2 -, -CF 2 -CF 2 -, and CF 3 -CF 2 -groups, respectively [50,51]. The CF 3 and CF 2 components could be clearly resolved from the other components because of fluorine's great electronegativity.…”
Section: Preparation and Characterization Of Perfluorophosphonic Acidmentioning
confidence: 96%
“…Indeed, the UV excimer laser is one of the most precise industrial processing tools and has many applications like eye surgery and semiconductor lithography [8]. Moreover, modifications induced on PET surfaces by UV lasers have been extensively studied [9] and major changes such as: surface amorphization [10]; roughness evolution [11][12][13]; chemical modifications [14][15][16]; and increased wettability [17] are well-known consequences of the laser irradiation. Studies show that Laser Induced Periodic Surface Structures (LIPSSs) are formed on fibers using a 248 nm excimer laser with a fluence below the ablation threshold of the material [13].…”
Section: Introductionmentioning
confidence: 99%